The safe and effective use of supercritical CO2-processed bone allografts for cervical and lumbar interbody fusion: A retrospective study - Aurouer, Nicolas; Guerin, Patrick; Cogniet, Arnaud; Pedram, Morad (Frontiers in Surgery, 2023)
Abstract Introduction: The clinical efficacy and safety of supercritical CO2-processed bone allografts prepared from living donors has yet to be confirmed in spinal surgery. Here we report our clinical and surgical experience of using supercritical CO2-processed bone allografts for lumbar and cervical fusion. Methods: Sixteen patients underwent one or two level anterior cervical discectomy and fusion and 37 patients underwent anterior retroperitoneal route lumbar fusion using bone allografts processed using supercritical CO2 extraction combined with chemical viral inactivation. Fusion success was assessed radiographically in the immediate postoperative period and at one month, six months, one year, and three years postoperatively. Function and pain were assessed using visual analog scales, Odom’s criteria, the neck disability index (NDI), and the Oswestry disability index (ODI). Results: At a mean of 43 and 47 months postoperatively, 95.3% and 90.5% of cervical and lumbar fusion patients had radiographic evidence of bone fusion, respectively. Over 80% of patients reported good to excellent outcomes according to Odom’s criteria, the perception of pain significantly decreased, and the mean NDI and ODI scores significantly improved at the last follow-up compared with before the operations. There were no safety concerns. Conclusion: Within the limitations of this study, the use of supercritical CO2-processed bone allografts resulted in satisfactory clinical outcomes and fusion rates with acceptable safety for both cervical and lumbar surgeries.